Oil resources and reserves in Russia. Issues and challenges - M. M. Solovyev (Путеводитель предпринимателя)
The article is considered the current situation of oil reserves and resources in Russia, the territorial location, quantitative and qualitative characteristics, the key issues of geological exploration, the factors affecting the efficiency of oil recovery and the main oil industry challenges.